Amount of carbon store in the species ficus soatensis and tecoma stans established in the locality of puente aranda, bogotá d.C. (2023)
The present study contributes to the mitigation and adaptation of climate change in the city of Bogotá, through of the valuation of carbon storage and the biomass of endemic species in the city, without use destructive methods. The mentioned information is necessary to scientifically show which roles these species play in the ecosystem and such allow us to define the good management of resources and to generate mechanisms in the long-term. To know the amount of carbon stored in the species Ficus soatensis and Tecoma stans settled in the locality of Puente Aranda, samples were taken from individuals of different diameter classes, of four tree components: trunk, bark, branches and leaves, and sent to the laboratory to be analyzed by the CHN test. The average carbon content for the two-species varied between 44.54% and 51.95% with an average of 47.23% and standard deviation of 2.84 in all tissues of the individuals analyzed. The carbon content accumulates differentially in the tissues of the individual; the highest value was obtained in the trunk of Tecoma stans and the lowest corresponds to the branches of Ficus soatensis. The percentages of Carbon content by species and by tissue found for Ficus soatensis were, in trunk 51%, branches 43%, bark 45% and leaves 46%; for Tecoma stans the results were 53% in trunk, 46.5% branches, 46.5% bark and 47.5% leaves. When comparing the carbon stocks in the biomass, using the specific concentration as a reference, with respect to the general carbon concentration for the species Ficus soatensis and Tecoma stans, it was found that there is a difference in the carbon content in the branches, since the one registered by the laboratory is greater than the one estimated in a general way. When evaluating the difference between the specific carbon reserves with the general carbon reserves, it can be evidenced that there is a significant difference in the case of the branches. Therefore, it is appropriate to consider this variation in carbon storage estimates, to reduce the margin of error when reporting results of this type. Copyright © 2018, AIDIC Servizi S.r.l.